2018
DOI: 10.1038/s41598-018-32331-3
|View full text |Cite
|
Sign up to set email alerts
|

The population genomics of yellowfin tuna (Thunnus albacares) at global geographic scale challenges current stock delineation

Abstract: Yellowfin tuna, Thunnus albacares, is one of the most important seafood commodities in the world. Despite its great biological and economic importance, conflicting evidence arises from classical genetic and tagging studies concerning the yellowfin tuna population structure at local and global oceanic scales. Access to more powerful and cost effective genetic tools would represent the first step towards resolving the population structure of yellowfin tuna across its distribution range. Using a panel of 939 neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 48 publications
3
69
0
1
Order By: Relevance
“…While these early tagging results would be useful as a historic reference to compare with results obtained in this study, their data are not available in any public repository. The contrasting movement patterns exhibited by different yellowfin life stages and studies conducted over a decade apart have demonstrated that tuna movement between tropical and temperate regions remains inadequately understood (Holland et al, 1999;Pecoraro et al, 2017Pecoraro et al, , 2018Anderson et al, 2019). As the Central North Pacific faces various anthropogenic stressors (Erauskin-Extramiana et al, 2019;Woodworth-Jefcoats et al, 2019) and stakeholders experience potential changes to fisheries management and conservation measures such as creation of large-scale marine protected areas (Richardson et al, 2018;Hernández et al, 2019), availability of yellowfin tuna and economic impacts to local communities will remain a serious issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these early tagging results would be useful as a historic reference to compare with results obtained in this study, their data are not available in any public repository. The contrasting movement patterns exhibited by different yellowfin life stages and studies conducted over a decade apart have demonstrated that tuna movement between tropical and temperate regions remains inadequately understood (Holland et al, 1999;Pecoraro et al, 2017Pecoraro et al, , 2018Anderson et al, 2019). As the Central North Pacific faces various anthropogenic stressors (Erauskin-Extramiana et al, 2019;Woodworth-Jefcoats et al, 2019) and stakeholders experience potential changes to fisheries management and conservation measures such as creation of large-scale marine protected areas (Richardson et al, 2018;Hernández et al, 2019), availability of yellowfin tuna and economic impacts to local communities will remain a serious issue.…”
Section: Discussionmentioning
confidence: 99%
“…A finding of range contraction in the equatorial region could be an artifact of the location and observation period covered by tagging data, which could be mitigated with adequate sampling in areas other than the equatorial region, even as the majority of catches occur around the Equator. Recently, high throughput genotyping with single nucleotide polymorphism markers has determined finer scale population structuring for yellowfin tuna in the Pacific Ocean (Grewe et al, 2015;Barth et al, 2017;Pecoraro et al, 2018;Anderson et al, 2019), complicating the management assumption that yellowfin comprise a single panmictic population in the Pacific. Sampling at each collection site/ area so far has remained small scale (n ≤ 11, Barth et al, 2017;n ≤ 24, Grewe et al, 2015;n ≤ 45, Pecoraro et al, 2018;n ≤ 80, Anderson et al, 2019), and the number of sites in the Pacific are limited (n = 2, Barth et al, 2017;n = 3, Grewe et al, 2015;n = 4, Pecoraro et al, 2018;n = 7, Anderson et al, 2019).…”
Section: Horizontal Movement and Stock Structurementioning
confidence: 99%
“…To date, no tagging experiments have considered fish of that size in movement range studies of yellowfin tuna (see Hallier and Fonteneau 2015). Nevertheless, our threshold size is even more conservative than those already considered in Atlantic Ocean yellowfin tuna stock structure analyses (Kitchens et al 2018;Pecoraro et al 2018). Thus, the final dataset consisted of 52 YOY and 15 age-1 fish (Table 1).…”
Section: Fish Samplingmentioning
confidence: 99%
“…Complementary genetic and microchemistry studies would help in understanding species and ecosystem connectivity at local scales for relatively low mobile species (i.e., below 100 km radius) and at large scale for highly migratory species (Pecoraro et al, 2018). This informs about the connectivity between spawning grounds and nurseries such as by transport of pelagic larvae (Selkoe et al, 2016).…”
Section: Technology For Fisheries and Ecosystem Studiesmentioning
confidence: 99%